Kajian Eksperimental Pembakaran Biomassa pada Ruang Bakar Fluidisasi - Muhtadin Muhtadin; Ahmad Syuhada; Hamdani Hamdani (Jurnal Teknik Mesin Unsyiah, 2014)
Combustion of biomass produces thermal energy that can be utilized of other energy utilities by conversion through fluidized combustion systems. Fluidized reactor with a system (fluidized bed) is an option to the existing conversion thermal energy in biomass. Fuel feed system on combustion chamber (combustor) and fluidized combustion reaction chamber (burner) at fluidization reactor unit integrated with utility boilers producing steam into the reactor performance targets, this is achieved by the provision of fuel to the prescribed amount and timeliness of feeder working system for supplying fuel to the combustion chamber (combustor). Maximum combustion temperature results obtained in between 20 to 30 seconds burning time for 2 (two) kg biomass. Combustion temperature is strongly influenced by the characteristics of biomass. Solid biomass character (wood chips and branches of dry wood planers) has a higher burning temperature of biomass fibers character (areca nut husk). The increase in temperature results for biomass combustion filamentous more quickly reach peak combustion temperature, the comparison is time for biomass burning wood character requires 30 seconds burning time , while for areca nut husk biomass only takes 20 seconds burning time for 2 kg of biomass .